Penggunaan media sosial, kebimbangan imej badan dan tingkah laku kecelaruan pemakanan dalam kalangan awal dewasa - Nurul Atiqah Noor Azizi,; Haikal Anuar Adnan,; Najwa Afiqa Roshaizad,; Suzana Mohd. Hoesni,; Mohd Syazwan Zainal, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Social media which has been used to define one’s beauty as something objective and difficult to achieve especially among young adults who often use this medium eventually leads to social comparison that cause body dissatisfaction and eating disorder behavior. Therefore, this study is conducted to identify the relationship between social media usage, body image concern and eating disorder behavior among young adults which involved 510 students from public universities located in Selangor. Survey method was used in this study and the questionnaires were distributed online by the researcher. Results show significant relationship between social media usage, body image concern and eating disorder behavior. However, this study found that social media does not play a major influence on body image concern and eating disorder behavior. These findings has indirectly supported the theories used in this study such as sociocultural theory, social comparison theory and objectification theory.